Physical Fitness and Metabolic Profile among Malay Undergraduates of a Public University in Selangor Malaysia - M. Emad; M. Kandiah; W. K. Lim; M. Y. Barakatun-Nisak; A. Rahmat; S. Norasruddin; M. Appukutty (Universitas Gadjah Mada, 2013)
This study investigated health-related components of physical fitness consisting of morphological fitness (body fat % or BF %; Body Mass Index or BMI; and waist circumference or WC), metabolic fitness (blood glucose, lipid profiles and haemoglobin) and aerobic capacity (VO2max). This crosssectional study involved 324 undergraduates recruited voluntarily by systematic random sampling from a public university in the city Shah Alam, Selangor Malaysia. The respondents’ aerobic capacity was measured by field fitness tests and anthropometric measurements using standard protocols. The mean BMI of respondents was 22.51 ± 4.18 kg/m2, and majority of the respondents (93%) are within normal range of WC. The prevalence of underweight was 13.5% and overweight/obese was 20.2%. The blood glucose levels of respondents were within the normal range (94.4%) and about 5% of female respondents had moderate anaemia. More than 70% of the males and 25% of the females had poor VO2max levels (aerobic capacity). In summary, the present results suggest the necessity of health promotion programme focusing on physical activity and nutrition for university students.